Work Immersion Preparedness of Grade 12 Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Work immersion is a crucial step for Grade 12 students, serving as a bridge between their academic journey and the professional realm. While some students exhibited great excitement, others expressed nervousness and lacked confidence in facing the realities of the professional world. The researchers aimed to determine the level of preparedness of students participating in the work immersion program from the students' perspective. This study employed a quantitative descriptive design, surveying 94 Grade 12 students enrolled at Union Christian College. Weighted mean and standard deviation was used to describe the level of preparedness of the respondents in their core skills and wellbeing aspects, and t-test for comparing their level of preparedness when grouped according to their profile. Their findings were triangulated with qualitative responses. The findings indicated that students exhibited high levels of preparedness in their core skills, with communication skills scoring the highest while technological skills scoring the lowest. Moreover, students demonstrated a high level of preparedness in their well-being aspects, with emotional preparedness receiving the highest score while social preparedness the lowest. While they perceive that they are prepared for immersion, the scores signify the need to improve their preparedness. Moreover, there are no significant differences in preparedness levels based on profile variables, implying that all students have similar levels of preparedness regardless of their personal characteristics. The findings can inform educational institutions about the essential preparations needed for students' successful transition into the professional realm. The study recommends adopting a video advocacy material to help students prepare for work immersion.
Keywords: work immersion; preparedness; core skills; well-being